Silicon meltdown. (Economist, 2018)
The article focuses on microprocessors which are vulnerable to hacker attacks aimed at stealing sensitive data such as password or encryption keys and mentions that protection would be to replace all affected processors. Topics discussed include views of chipmaker Intel on availability of software that will fix the weakness, cloud-computing services such as Amazon Web Services and lawsuit over vulnerabilities that has hit Intel.